The role of nitric oxide system in pathology development - Chukwu, Aloysius; Danukalo, M. V.; Данукало, Максим Вікторович (Запорізький державний медичний університет, 2015)
Nitric oxide is the most known gaseous molecule, which plays significant signaling role in almost all the tissues of higher vertebrates. The NO system consists of three distinct NO synthase (NOS) isoforms, including neuronal (nNOS or NOS-1), inducible (iNOS or NOS-2) and endothelial (eNOS or NOS-3). The aim of our study was to analyze current data from scientific sources in order to find possible role of NO system in certain pathological processes, such as hypertension, atherosclerosis and diabetes mellitus. Small amount of NO molecules, which are synthesized with the constitutive NOS (nNOS and eNOS) work as paracrine mediator and support physiological functions.